Peningkatan Derajat Kesehatan Masyarakat Melalui Pemeriksaan Kesehatan dan Edukasi Pola Hidup Sehat - Puspitasari, Puspitasari; Rinata, Evi; Salim, Agus (Jurnal Pemberdayaan Masyarakat, 2019)
Improving the level of public health can be started by increasing sufficient knowledge about healthy lifestyles. The period of the elderly is a period of life that needs attention because this period is susceptible to disease. Community service activities aim to broaden the views on the importance of health for the elderly. This activity was carried out at the elderly Posyandu, Jiken Village, Tulangan, Sidoarjo in March to April 2019. The method used was observation, Point of Care Testing (POCT) training for Posyandu cadres, counseling and consultation regarding healthy lifestyles. The result of this activity is that Posyandu cadres can do Point of Care Testing (POCT) and can implement it continuously because the simple medical devices they have are complete. In addition, the elderly people are increasingly enthusiastic to come to the posyandu. This can be seen from the list of visits and activeness of the elderly in participating in the whole series of activities while in the posyandu.